2013
DOI: 10.1111/dpr.12039
|View full text |Cite
|
Sign up to set email alerts
|

Climate Variability and the Role of Access to Crop Insurance as a Social‐Protection Measure: Insights from India

Abstract: Based on a primary survey conducted in India, this article examines the merits of crop insurance in adapting to the changing climate. However, lack of awareness and the complicated process of agricultural insurance were found to be major obstacles to the uptake of such schemes among small and marginal farmers. While crop insurance might help farmers at the household level, there is a need in developing countries like India to devise insurance schemes that take account of the long-term negative consequences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The experience of developed countries in preventing such losses is to a large extent related to agricultural insurance. Such countries as Canada, the United States and Spain as flagships in the field of agricultural insurance have introduced insurance schemes that allow farmers to protect effectively their crops from the weather risks (Shen & Odening, 2013;Panda, 2013). Although insurance in these countries is entirely voluntary, the state induces farmers to use insurance through the possibility of receiving subsidies for the cultivation of certain crops.…”
Section: Theoretical Basismentioning
confidence: 99%
“…The experience of developed countries in preventing such losses is to a large extent related to agricultural insurance. Such countries as Canada, the United States and Spain as flagships in the field of agricultural insurance have introduced insurance schemes that allow farmers to protect effectively their crops from the weather risks (Shen & Odening, 2013;Panda, 2013). Although insurance in these countries is entirely voluntary, the state induces farmers to use insurance through the possibility of receiving subsidies for the cultivation of certain crops.…”
Section: Theoretical Basismentioning
confidence: 99%
“…Bhende (2012) studied the problems of agriculture insurance in India particularly for Karnataka state and suggested the need for crop revenue insurance in the Indian context. Panda (2013) assessed the significance of crop insurance in climate change situation for social-protection to farmers. Sinha and Tripathi (2014) evaluated and compared the crop insurance issues of India and Thailand and found that effective penetration of crop insurance reduced the financial liability of the government.…”
Section: Review Of Literature On Agriculture Insurance In Indiamentioning
confidence: 99%
“…Concerns about social protection leading to mal‐adaptation in the long‐term are raised in studies about insurance in particular, not least because insurance protects less well against slow‐onset climate impacts and tends to overlook non‐climatic dimensions of vulnerability (Heltberg et al, ). Panda ()'s study on crop insurance in two districts in Western Odisha, India also shows that small and marginal farmers often lack access to crop insurance (e.g., because of an absence of property rights to land), or awareness and understanding of the concepts and procedures to enable them to make an informed decision about whether they should acquire insurance. When they do have access, the probability that they shift from traditional to cash crop cultivation (mono‐culture) increases, which paradoxically makes farmers more at risk of total crop failure (Panda, ).…”
Section: Is Social Protection Already Contributing To Climate Change mentioning
confidence: 99%
“…Panda ()'s study on crop insurance in two districts in Western Odisha, India also shows that small and marginal farmers often lack access to crop insurance (e.g., because of an absence of property rights to land), or awareness and understanding of the concepts and procedures to enable them to make an informed decision about whether they should acquire insurance. When they do have access, the probability that they shift from traditional to cash crop cultivation (mono‐culture) increases, which paradoxically makes farmers more at risk of total crop failure (Panda, ). Moreover, Akter ()'s review of research on the potential of weather microinsurance in Bangladesh highlights that insurance does not provide a safety net against climate risks for the poor due to low demand, poor coverage and lack of commercial viability.…”
Section: Is Social Protection Already Contributing To Climate Change mentioning
confidence: 99%